Process Improvement Through The Application Of Quality Function Deploy¬ment - Campos, Roni C.P. (2013)
QFD (Quality Function Deployment) has been successfully applied to develop products and services. However, itsapplication is usually limited to the first matrix, the quality matrix. There is the possibility of QFD usage to define the processcontrol parameters. In this context, the present work aims to apply QFD in the production improvement in a company thatproduces plastic films for packaging in order to define better ways to standardize its production operation. This work is basedon action research, divided into five parts. In the first part the theoretical basis is established, followed to research methodsand design, data collection, and achieved results. The results demonstrates a diagnostic and an analysis of productionprocess for a specific company product and concludes that there is a relevant potential for this type of QFD application.